A Study on the Correlation between the Imbalance of “Lung Governing Dispersion and Depuration” and the Onset of Bronchial Asthma and Its Regulation Ideas - Yan, Xuan; Ma, Zhanping (Journal of Contemporary Medical Practice, 2025)
The imbalance of “the lung governing dispersion and descent” is the core pathogenesis of bronchial asthma. During the acute attack phase of asthma, due to stagnation of lung qi and intermingling of phlegm and qi, there occur wheezing and chest tightness, and the treatment should focus on diffusing the lung to resolve phlegm, lowering adverse qi and removing blood stasis. During the remission phase, due to deficiency and malnourishment of the spleen and kidney as well as stagnation and dysfunction of liver qi, it is necessary to invigorate the spleen and tonify the kidney to consolidate the root cause, and soothe the liver and regulate qi to prevent recurrence. This idea of staging treatment based on “treating the symptoms in acute conditions and treating the root cause in chronic conditions” is not only in line with the classic theories of traditional Chinese medicine, but also indirectly supported by modern medical research on airway pathology, providing a clear diagnosis and treatment path for the prevention and treatment of asthma with integrated traditional Chinese and Western medicine.